The Effect of Traditional Game to Improve Students’ Vocabulary Mastery among Junior High School - Hadania, Hadania; Sain, Yulianah; Nasrullah, Rahmat; Rusli, Tri Indah (Journal of English Language and Education, 2025)
This study aims to investigate the effect of using the traditional game Lengko-lengko on improving the vocabulary mastery of seventh-grade students at SMP Negeri 20 Kendari. The research employed a pre-experimental design with a one-group pre-test and post-test design. The sample consisted of 30 students selected through purposive sampling. The research instrument was a multiple-choice vocabulary test comprising 10 items administered in both pre-test and post-test. Data were analysis using normality test and paired sample t-test. The results revealed a significant difference between the pre-test and post-test scores (t = -5.054, p 0.05). Therefore, it can be conclude that the traditional game Lengko-lengko has a positive and significant effect on enhancing students’ English vocabulary mastery. These findings support previous studies that highlight the importance of innovative and culturally relevant learning strategies in fostering students’ motivation and learning outcomes